Inovasi Pembuatan Praline Isi Manisan Kering Belimbing Dengan Penambahan Bubuk Daun Kersen - U.Yuyun Triastuti; Retno Aprilia Susanti (Garina, 2021)
Making pralines filled with dried starfruit with the addition of cherry leaf powder, is an innovation in developing chocolate products, which are varied with candied starfruit filling. In the processing, candied star fruit and chocolate are added with cherry leaf powder, to add aroma to the pralines. The objectives of this study are: 1) To determine the characteristics of candied star fruit with the addition of cherry leaf powder. 2) Knowing the characteristics of candied star fruit pralines with the addition of cherry leaf powder. 3) Knowing the public's acceptance of pralines filled with candied star fruit with the addition of cherry leaf powder. The research methods used are library, experimental, documentation, organoleptic, and hedonic methods. Data analysis using descriptive. The results showed the characteristics of dried star fruit candied with the addition of cherry leaf powder, textured dry on the outside and soft on the inside, sweet taste like raisins, brownish yellow in color, and scented with cherry leaves. Characteristics of pralines filled with candied starfruit with the addition of cherry leaf powder, sweet taste, distinctive aroma of chocolate and cherry leaf powder, dense and slightly rough texture, dark brown color. Public acceptance of candied starfruit pralines with the addition of cherry leaf powder through hedonic test results, the most preferred and accepted by the community is product code 657. Suggestion, it is necessary to test the shelf life, and test the nutritional content of pralines filled with candied starfruit with the addition of powder cherry leaf.